Reforma autotérmica do metano: estudo do Processo e de catalisadores - Dias, Joelmir Augusto Costa (Universidade Federal de São Carlos, 2005)
The study of the autothermal reforming of methane over Ni/γ-Al2O3 catalyst, promoted with noble metals was the objective of this work. In the first part, the stability to coke deposition of the autothermal reforming was studied, through air addition to the feed of steam reforming, at 600oC over Ni/γ-Al2O3, at favourable conditions to coke deposition (CH4/H2O=4). It has been observed that the amount of coke decreased with the increase in air addition. This leads to the conclusion that the autothermal reforming of methane is a stable process to coke deposition. The second part of the work concentrated in the understanding of the effect of small amount (0,3% w/w) of the noble metals platinum, iridium and palladium for the steam reforming, partial oxidation and autothermal reforming of methane. The preparation of the platinum- and iridium-promoted catalysts was made via chloride. For the palladium, chloride and nitrate was used. It has been observed that the addition of noble metals allowed the reduction of the catalyst at lower temperature, increasing the reduction degree and, consequently, the metallic surface area of the catalyst. The small amount of noble metals did not cause any important electronic influence to nickel. Partial oxidation of methane also did not suffer any effect of noble metals, given that the non-promoted catalyst took this reaction to thermodynamic equilibrium. The steam reforming hat its conversion increased, and this increase was proportional to the metallic surface area. The same happened with autothermal reforming. This leads to the suggestion that the steam reforming is the limiting step for the autothermal reforming. Thus, it has been concluded that the unique important effect of the addition of platinum, iridium and palladium to the Ni/γ-Al2O3 catalyst, for autothermal reforming, is the increase in metallic surface area of the catalysts. The same catalysts were submitted to start tests of autothermal reforming of methane, without previous reduction with hydrogen. These tests were made through intermittent starts at 600oC, alternated with air flow at high temperature. The platinum- and iridium- promoted catalysts were active in all starts. For the catalysts promoted with palladium, only the ones prepared via nitrate was active. The palladium-promoted catalysts, via chloride, did not showed activity in autothermal reforming without previous reduction with hydrogen, being active only for combustion of methane, due to the non-reduction, due to the formation of palladium oxochloride, which has a strong interaction with alumina. In the third part of the work, the behavior of the steam and autothermal reforming and partial oxidation of methane in extended bed reactor was studied. The temperature profiles of the reactions were measured with the catalysts promoted with platinum and palladium. It has been verified that the partial oxidation and autothermal reforming occurs via combustion, parallel with steam and CO2-reforming. The promoted catalysts showed a flatter temperature profile than non-promoted catalyst, due to the difference of activity among them.
Autothermal reforming of methane: study of the process and catalysts
Keywords: Catálise; Catalisadores de níquel; Hidrogênio; Metais nobres; Reforma a vapor; Oxidação parcial do metano; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA